Attitude and level of satisfaction on objective structured practical examination and traditional practical examination among undergraduate nursing students - P Muhammad Sharvan; Anju Ullas; Indumathi Vasanth (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Objective structured practical examination (OSPE) and traditional practical examination (TPE) are two different methods used to evaluate the theoretical and practical skills among students. The present study assessed the attitude and level of satisfaction of undergraduate nursing students toward OSPE and TPE. MATERIALS AND METHODS: A comparative research design study was conducted at Yenepoya Nursing College in 2022. The samples were 4th year B.Sc nursing students who have experienced both types of examination system and are selected by using the non-probability purposive sampling technique. The selected 102 students are further divided into two groups (51 students in each group) by the chit method: one group for assessing the attitude and level of satisfaction toward OSPE and the other group for assessing the attitude and level of satisfaction toward TPE. The tools used were demographic proforma, structured attitude, and satisfaction scale. The collected categorical data were represented as frequency and percentage, and quantitative data are represented in terms of mean and standard deviation. The Mann-Whitney U test was used to compare the attitude and level of satisfaction between the two groups. RESULTS: The majority [32 (65.7%)] of the participants had positive attitude toward the OSPE, and the majority [30 (61.5%)] of the samples had neutral attitude toward TPE. Most of the students [27 (55.3%)] had a good level of satisfaction toward the OSPE. The majority [28 (56.3%)] of the samples had an average level of satisfaction toward TPE. The median of attitude score was 48.32 with 3.35 inter-quartile range (IQR) on OSPE and 44.40 with 3.35 IQR on TPE. The median of level of satisfaction was 50.95 with 1.69 IQR on OSPE and 46.05 with 1.69 IQR on TPE. CONCLUSIONS: The study concluded that the students have positive attitude and a good level of satisfaction toward OSPE and neutral attitude and an average level of satisfaction toward TPE. The results provide important implications for choosing a different examination strategy and increasing the standard for the educational and evaluation systems.